An interesting new genus of Berothinae (Neuroptera: Berothidae) from the early Eocene Green River Formation, Colorado - Makarkin, Vladimir N. (Zootaxa, 2017)
Xenoberotha angustialata gen. et sp. nov. (Neuroptera: Berothidae) is described from the early Eocene of the Parachute Creek Member of the Green River Formation (U.S.A., Colorado). It is assigned to Berothinae as an oldest known member of the subfamily based on the presence of scale-like setae on the foreleg coxae. Distal crossveins of the fourth (outer) gradate series which are located very close to the wing margin in Xenoberotha gen. nov. is a character state previously unknown in Berothinae.